Exploring Immediate and Sustained Changes in Teaching Practices Following Midterm Student Feedback (Teaching and Learning Inquiry, 2025)
Midterm student feedback is increasingly considered to have greater potential for improvement in post-secondary teaching than end-of-term course evaluations. While many benefits have been established, the process for gathering midterm feedback has been studied exclusively with the aim of characterizing short-term effects. At McMaster University, in Hamilton, Ontario, Canada, midterm student feedback is called a “course refinement.” As the final part of a multiphase study investigating instructors’ perceptions of the course refinement process and its impact, this paper examines whether changes made by instructors following the course refinement process are sustained beyond the term. The study involved two phases of data collection: initially, a semi-structured in-person interview or survey completed one to three months following the conclusion of an instructor’s refined course, followed by an additional interview one year after the instructor’s course refinement. Changes to instructors’ teaching practices were evident in both phases. Furthermore, a thorough examination of sustained change revealed two predominant themes: the relationship between sustained change and instructors’ beliefs about teaching, and the impact of sustained change on various levels of higher education. The latter theme is explored via an ecological systems framework, which revealed much broader implications than we ever imagined. Course refinements do, indeed, lead to lasting changes that go beyond the boundaries of a course and have effects departmentally, institutionally, and inter-institutionally—and conceivably even influence post-secondary society and culture more widely.